Africa after apartheid : South Africa, race, and nation in Tanzania - Schroeder, Richard A. (Indiana University Press, 2012)
Tracing the expansion of South African business into other areas of Africa in the years after apartheid, Richard A. Schroeder explores why South Africans have not always made themselves welcome guests abroad. By looking at investments in Tanzania, a frontline state in the fight for liberation, Schroeder focuses on the encounter between white South Africans and Tanzanians and the cultural, social, and economic controversies that have emerged as South African firms assume control of local assets. Africa after Apartheid affords a penetrating look at the unexpected results of the expansion of A.